2015
DOI: 10.1007/s40011-015-0552-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Enzyme Activities and Carbon Stock in Unique Coastal Acid Saline Soils of Goa

Abstract: The aim of the present investigation was to study the effects of salinity under low soil pH conditions on soil microbial and enzyme activities and to quantify soil organic carbon (SOC) stocks in coastal saline soils of Goa, India. Global positioning system based replicated soil samples collected from fifteen different locations showed characteristic variations in electrical conductivity (0.09-6.29 dS m -1 ), soil pH (4.11-6.57), exchangeable sodium (Na) (7.40-23.2 meq 100 g -1 ) and exchangeable sodium percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
4
11
0
Order By: Relevance
“…The qCO 2 of strongly saline soils was 2.4 times higher than that of non-saline soils. The occurrence of higher qCO 2 with high salinity levels has been reported in literature by researcher (Mahajan et al, 2015;Iwai et al, 2012;Tripathi et al, 2007) and our observations are in line with them. Chowdhury et al (2011) and Setia et al (2011) reported the decrease in BSR with increasing levels of salinity and this trend was similar even after addition of organic matter.…”
Section: Microbial Activitysupporting
confidence: 93%
See 4 more Smart Citations
“…The qCO 2 of strongly saline soils was 2.4 times higher than that of non-saline soils. The occurrence of higher qCO 2 with high salinity levels has been reported in literature by researcher (Mahajan et al, 2015;Iwai et al, 2012;Tripathi et al, 2007) and our observations are in line with them. Chowdhury et al (2011) and Setia et al (2011) reported the decrease in BSR with increasing levels of salinity and this trend was similar even after addition of organic matter.…”
Section: Microbial Activitysupporting
confidence: 93%
“…Besides the physical properties of the soil, the biological properties serves as a better indicator of soil quality and one such biological properties is MBC (Mahajan et al, 2015). Inverse relationship of the salinity with MBC, during all the seasons, is in line with those reported by Tripathi et al (2006), Iwai et al (2012), and Mahajan et al (2015). The range of the MBC in the present investigation is 21.1 to 112.8 mg kg −1 .…”
Section: Microbial Activitysupporting
confidence: 89%
See 3 more Smart Citations